Chinese translation and validation of the Near-Death Experience Content scale - Li, Yan; Chen, Yan; Martial, Charlotte; Shen, Mingquan; Cassol, Héléna; Yu, Jing; Zhou, Xingyue; Ni, Chengcheng; Li, Meiqi; Hu, Nantu; Gosseries, Olivia; Laureys, Steven; et al. (Frontiers in Psychiatry, 2024)
In recent years, a growing number of near-death experience (NDE) testimonies have been collected worldwide due to an increasing interest in research on this phenomenon. China has many patients who survive life-threatening situations, leaving over much data on NDEs to be collected for research. In the historical context of Eastern civilization, many mentally controlled practices in China can also lead to "NDEs-like" (e.g., meditation). We aimed (1) to translate and validate the recently developed Near-Death Experience Content (NDE-C) scale into Chinese and (2) to quantify and identify NDEs and NDEs-like in China with this new Chinese version of the NDE-C scale. Here, we presented the work that had been performed to translate the NDE-C scale into Chinese and validated this version on 79 NDE testimonies. Brislin's back-translation model was performed to translate a Chinese version of the NDE-C scale and internal consistency (the Cronbach's α value for the total group = 0.846) as well as the confirmatory factor analysis was conducted. The committee reached an agreement on the Chinese version of the NDE-C scale, which is currently ready for use in research practice in the context of Eastern culture.